Participatory process in times of remote learning: An adaptation of the Educational Service at Escola_Casa - Stein, Evandro Jefferson; Everling, Marli Teresinha; Dias, Maria Regina Álvares Correia; Sobral, João Eduardo Chagas; Morgnestern, Elenir Carmen (DAT Journal, 2021)
The remote activities accelerated by Covid-19 brought the need to rethink the participatory activities contained in the Human-Centered Design processes. In this context, the research used participatory design as a strategy for the development of a hybrid teaching-learning methodology for Escola_Casa, a private entity that promotes training in the areas of art and design and serves the entire micro region of Blumenau Santa Catarina. This article consists of a case study that presents the problems, objectives, procedures and tools used in the Workshop that was one of the most important participatory activities in this research, as well as showing how the Human-Centered Design methodology needed to be adapted, with the use of remote actions that would guarantee a safe progress for the participants while favoring the efficiency for the solution of the development processes. The structure covers the research contextualization presented as introduction, theoretical foundation, design, participation and human-centered approaches, a pandemic scenario, the methodological structure, the organization and the conduction of the participatory process, results and conclusion.